Effects of Talker Variability on Recall of Spoken Word Lists - Martin, C. S. (1989)
Three experiments were conducted to investigate recall of lists of words containing items spoken by either a single talker or by different talkers. In each experiment, recall of early list items was better for lists spoken by a single talker than for lists of the same words spoken by different talkers. The use of a memory preload procedure demonstrated that recall of visually presented preload digits was superior when the words in a subsequent list were spoken by a single talker than by different talkers. In addition, a retroactive interference task demonstrated that the effects of talker variability on the recall of early list items were not due to use of talker-specific acoustic cues in working memory at the time of recall. Taken together, the results suggest that word lists produced by different talkers require more processing resources in working memory than do lists produced by a single talker. The findings are discussed in terms of the role that active rehearsal plays in the transfer of spoken items into long-term memory and the factors that may affect the efficiency of rehearsal.